Interaction between Crofer 22 APU Current Collector and LSCF Cathode Contacting Layer under Cell Operation. (2nd June 2015) - Spotorno, Roberto; Piccardo, Paolo; Perrozzi, Francesco
Abstract : In this work the oxidation of Crofer 22 APU and its interaction with La0.6 Sr0.4 Co0.2 Fe0.8 O3 (LSCF) applied as contacting layer have been investigated in air at 750°C under a current load of 0.5 Acm -2 with the aim to reproduce as close as possible the interconnect interface in real operating conditions. The effects of such interaction and of the pre-oxidation treatment have been studied by means of ASR measurement and post-experiment characterizations. The behavior of such samples has been compared with the results on a working Crofer 22 APU bipolar plate tested as cathode current collector of an anode-supported cell reproducing the stack cathode compartment conditions.